A Comparative Review of Islamic and Western Epistemological Frameworks Between Mysticism and Secularism - Abdul Fatah, Achmad (Civiliza Publishing, 2025)
This article explores the fundamental foundations of knowledge by analyzing and comparing Irfani and Western epistemological paradigms. Using a qualitative library research method with a descriptive-analytical approach, this study examines how these two frameworks diverge and intersect. The findings reveal a primary distinction in the sources of knowledge: while the Western tradition encompassing Rationalism, Empiricism, and Criticism relies on reason, logic, and sensory perception, Irfani epistemology (Sufism) is rooted in intuition or direct spiritual experience (zhauqi). This study offers a novel perspective by highlighting that, despite the secularist-materialist bias often found in Western thought, both paradigms serve as essential conceptual frameworks for truth-seeking. The academic novelty of this research lies in its synthesis of “present knowledge” (‘Ilm al-Laduny) and “acquired knowledge,” demonstrating how Irfani thought utilizes reason to interpret spiritual phenomena, much like the collaborative effort between ratio and experience found in Criticism. Ultimately, the comparison underscores a complementary potential between Irfani’s inner spiritual illumination and the Western emphasis on empirical verification.